Papillary Thyroid Carcinoma Arising Within a Mature Ovarian Cystic Teratoma: A Case Report - Pakaworn Vorasart; Rangsima Aroonroch; Naparat Rermluk; Orawin Vallibhakara; Chutintorn Sriphrapradang (Case Reports in Endocrinology, 2025)
Conclusions: This case describes the rare occurrence of papillary thyroid carcinoma within a mature ovarian teratoma. Currently, there is a lack of consensus on postoperative management. In selected cases with no evidence of metastasis or aggressive features, conservative management may be a reasonable option after thorough evaluation.